Locomotor adaptations during racerunning in people with neurological motor disorders - Shafizadeh, M.; Theis, N.; Davids, K. (Adapted Physical Activity Quarterly, 2023)
The aim of this study was to examine strategies to absorb impact shock during RaceRunning in participants with neurological motor disorders. For this purpose, 8 RaceRunning athletes (4 male and 4 female) voluntarily took part in the study. Each participant performed a series of 100-m sprints with a RaceRunning bike. Acceleration of the tibia and head was measured with 2 inertial measurement units and used to calculate foot-impact shock measures. Results showed that RaceRunning pattern was characterized by a lack of impact peak in foot-ground contact time and the existence of an active peak after foot contact. Due to the ergonomic properties of the RaceRunning bike, shock is attenuated throughout the stance phase. In conclusion, the results revealed that RaceRunning athletes with neurological motor disorders are capable of absorbing impact shock during assisted RaceRunning using a strategy that mimics runners without disabilities.